Synthesis and Characterization of Some Metal Complexes of [1-(4-Bromo-2-Methyl-Phenyl)-3-(4-Methoxybenzoyl)-Thiourea - Taghreed B. Alwan (Journal of Global Pharma Technology, 2018)
A new ligand [1-(4-Bromo-2-Methyl-Phenyl)-3-(4-Methoxy benzoyl)-Thiourea) (BMT) was synthesized by reaction of (4-Methoxyibenzoyliisothiocyanate) with (4-bromo-2-methyl anline). The Ligand was characterized by elemental micro analysis (C.H.N.S), (FT-IR) (UV- Vis) and (1H,13CNMR) spectra. Some transition metals complexes of this ligand were prepared and characterized by (FT-IR, UV-Vis) spectra conductivity measurements magnetic susceptibility and atomic absorption. From the obtained results the molecular formula of all complexes was suggested to be [M (BMT) 2Cl2] (M+2i=Cu, Mn, Co, Ni, Zn, Cd and Hg), the proposed geometrical structure for all complexes was an octahedral.Keywords: 4-bromo-2-methyl anline, 4-Methoxy benzoyl isothiocyanate, complexes.